Highly efficient detection of ethanol by SnO2 nanoparticles-decored NiO nanocuboids - Perrone, Olavo M. [UNESP]; Roveda, Antonio C.; de Moraes, Daniel A.; Theodoro, Reinaldo dos Santos [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2023)
There is great interest in developing devices to detect gasses for the constant monitoring of environments and to ensure welfare. However, developing portable devices with low cost and low detection limits, good selectivity using abundant semiconducting metal oxides, and easy and fast synthesis is still challenging. In this sense, we present a high surface area sensor based on SnO2 nanoparticles (NPs) deposited on NiO nanocuboids (NCs), with high response to ethanol. We used the precipitation of Ni foam in oxalic acid, followed by a microwave-assisted solvothermal process in ethylene glycol, urea, and K2SnO3·3H2O; then, the SnO2 (NPs)-NiO (NCs) could be obtained through the calcination of the as-prepared precursor. Even after 20 cycles of operation, the developed heterostructure material's response to ethanol detection was found to be Rair/Rgas = 84 ± 6 at its optimum temperature (350 °C), and it can exhibit better performance at lower temperatures compared to other materials.
Keywords: Gas sensor; Heterostructure; Microwave-assisted synthesis; Sensitivity; Volatile organic compounds